PENGARUH KITOSAN SEBAGAI EDIBLE COATING TERHADAP MUTU FISIK DAN KIMIA JERUK RIMAU GERGA LEBONG SELAMA PENYIMPANAN - GUSMON SIDIK; Wuri Marsigit; Syafnil (BPFP Faperta UNIB, 2022)
Rimau Gerga Lebong oranges (Citrus nobilis Sp.) or commonly referred to as RGL are a leading commodity in Lebong Regency, Bengkulu Province which during storage include perishable fruit, the skin becomes speckled, dirty, and the color of the fruit is unattractive so that it can reduce the quality of RGL oranges. Therefore, it is necessary to post-harvest handling to prevent a decrease in the quality of RGL citrus fruits. Chitosan is a natural cationic polysaccharide obtained from deacetylation of chitin which is widely found in nature, one of which is from shrimp shells. Chitosan sourced from shrimp shells can be used as a coating material and suppress the respiration process of fruit, namely in the form of edible coating. Edible coating is a thin layer that sticks directly to food, which aims to inhibit fruit respiration during storage so that fruit quality can be maintained. This study aims to determine the best concentration of shrimp shell chitosan as an edible coating in maintaining the quality of RGL oranges by observing the physical and chemical quality of RGL oranges during storage. This study used a non-factorial Completely Randomized Design (CRD), namely the concentration of shrimp shell chitosan (0%; 1%; 2%; 3%;) (w/v) with 3 repetitions to obtain 12 experimental units. Observations of RGL oranges were carried out on the 0, 5, 10, 15, and 20 days of storage. The results showed that the use of shrimp shell chitosan as an edible coating had an effect on the physical quality and chemical quality of RGL oranges during storage. The higher the concentration of chitosan, it can inhibit the reduction in weight loss, maintain color, inhibit softness, moisture content, pH value, total acid, vitamin C, and Total Dissolved Solids (TPT). The best concentration of shrimp shell chitosan as edible coating was obtained in 2% chitosan, until the 20th day it was obtained weight loss of 16.33%, brownish yellow color, texture 15.51%, water content 60.66%, pH value 4.25, total acid 0.58%, vitamins C 27.28 Mg/100g, and TPT 11.13%.